EVALUATION OF COST PERFORMANCE IN THE SUTOJAYAN DISTRICT SUBALI BRIDGE CONSTRUCTION PROJECT (D.G.008), BLITAR REGENCY USING EARNED VALUE ANALYSIS METHOD - Setyawan, Dhimas Triadi; Oetomo, Wateno; Marleno, Risma (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
One of the project types is the Construction Project. The main activity components of this type of project consist of feasibility assessment, engineering design, procurement and construction. In construction projects very often delays occur where the realization in the field does not match the schedule of the implementation plan, due to several factors that occur, even though a careful plan has been prepared but in practice in the field there are still many problems in implementation. The purpose of this study was to determine the cost and time performance in the implementation that took place from week -1 to week 17 on the Subali Bridge Construction project, Sutojayan Kec. (D.G.008), Blitar Regency using Earned Value. From the results of the analysis it can be seen that the costs incurred are lower than the planned costs, this can be seen in the CPI value of 1.28 while the implementation time is slower than the planned schedule indicated by the SPI value of 0.71. The results of the calculation of the estimated project cost of Rp. 8,214,904,015.36 with a budget plan of Rp. 10,502,000,000.00 there is an efficiency of Rp. 2,287,095.64 (21.78%). with an estimated completion time of 19.43 weeks, indicating that the project is delayed for 2.43 weeks from the planned 17 weeks.